The Alveolar Epithelium Mechanisms of Injury and Repair - Kasper, Michael; Mühlfeld, Christian (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Alveolar epithelial cells (AECs) of the lung are important contributors to pulmonary immune functions and to pulmonary development and alveolar repair mechanisms following lung injury. AECI, together with the capillary endothelium, form the extremely thin barrier between alveolar air and blood. AECII produce and metabolize the surface-tension lowering and immune-modulating surfactant and are the progentiors of AECI. A great variety of processes rely on their normal functioning, including maintenance of the alveolar barrier; innate immune defense; and processes of differentiation, senescence, apoptosis, and autophagy. The wide range of AEC functions is nicely reflected by the diversity of topics addressed by the four review and eight original articles contained in this Special Issue of the International Journal of Molecular Sciences. Beyond the broad spectrum of topics, the authors of this issue also made use of an impressive variety of analytical methods, thus further illustrating the fascinating diversity of aspects related to AEC biology.